(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The present study gathereddata through survey method. Survey of 600 secondary and senior secondary school students in the city centre and villages of Kurukshetradistrict found that rural students andstudents studying in government schools were still not aware of the variousthreats of environment and natural calamities and most of the Government rural schools did not possess basic literature related to Environment (inregional language). The paper suggested environmental awareness campaigns likecompetitions, vanmahotsavs, tree plantation, celebration of world environmentalday etc. be carried out in these areas.